2004
DOI: 10.1017/s095252380421505x
|View full text |Cite
|
Sign up to set email alerts
|

Functionally intact glutamate-mediated signaling in bipolar cells of the TRKB knockout mouse retina

Abstract: In the juvenile trkB knockout (trkB −/− ) mouse, retina synaptic communication from rods to bipolar cells is severely compromised as evidenced by a complete absence of electroretinogram (ERG) bwave, even though the inner retina appears anatomically normal (Rohrer et al., 1999). Since it is well known that the b-wave reflects light-dependent synaptic activation of ON bipolar cells via their metabotropic glutamate receptor, mGluR6, we sought to analyze the anatomical and functional integrity of the glutamatergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…On the other hand, light stimulation on both wild-type (WT) and Trpm1 À/À mice cone OFF-bipolar cells evoked photoresponses, and there were no significant differences in either the amplitude of the light responses or the time for half-maximal amplitude after the light was turned off (Koike et al 2010b). Examination of the optokinetic responses and electroretinograms (ERGs) of 2-month-old WT and Trpm1 À/À mice revealed optokinetic deficiencies similar to those of mice lacking mGluR6 and WT mice injected intravitreally with the mGluR6 agonist, L-2 amino-4-phosphonobutyric acid (Slaughter and Miller 1985;Euler et al 1996;Iwakabe et al 1997;McGillem and Dacheux 2001;Rohrer et al 2004;Koike et al 2010b). The ERGs evoked by light stimuli in WT mice show normal a-waves and b-waves, originating mainly from photoreceptor cells and bipolar cells, respectively.…”
Section: Lessons From Knockoutsmentioning
confidence: 88%
“…On the other hand, light stimulation on both wild-type (WT) and Trpm1 À/À mice cone OFF-bipolar cells evoked photoresponses, and there were no significant differences in either the amplitude of the light responses or the time for half-maximal amplitude after the light was turned off (Koike et al 2010b). Examination of the optokinetic responses and electroretinograms (ERGs) of 2-month-old WT and Trpm1 À/À mice revealed optokinetic deficiencies similar to those of mice lacking mGluR6 and WT mice injected intravitreally with the mGluR6 agonist, L-2 amino-4-phosphonobutyric acid (Slaughter and Miller 1985;Euler et al 1996;Iwakabe et al 1997;McGillem and Dacheux 2001;Rohrer et al 2004;Koike et al 2010b). The ERGs evoked by light stimuli in WT mice show normal a-waves and b-waves, originating mainly from photoreceptor cells and bipolar cells, respectively.…”
Section: Lessons From Knockoutsmentioning
confidence: 88%
“…Whereas BDNF may be produced and released in the retina by Müller glial cells (Seki et al,2003,2005), trk B receptors have not previously been observed to be expressed by photoreceptors (Rohrer et al,1999; Liu et al,2007). It is interesting to note, however, that homozygous trk B knockout mice have a robust electroretinography (ERG) a‐wave, but lack the ERG b‐wave, suggesting a failure in photoreceptor neurotransmission (Rohrer et al,1999,2004). Regardless of the mechanism, VGSCs have been recently implicated to play a major role in cone photoreceptor physiology.…”
Section: Discussionmentioning
confidence: 99%
“…TrkB knockout (TrkB -/- ) mice were provided by Dr. Barbara Rohrer, Medical University of South Carolina, Charleston, SC and the colony was maintained in our animal housing facility at the Georgia Health Sciences University. The generation of mice lacking the TrkB has been described previously [29]. Male wild-type (WT) and TrkB -/- mice (C57BL/6 strain background) used in a given experiment, originated from the same breeding series and were matched for age and weight (age = 2–3 months; weight = 25–30 g).…”
Section: Methodsmentioning
confidence: 99%